Proteomic analysis of rice seed storage proteins in relation to nutrient quality of three different commercial rice types - Ramli, Nur Syazila; Md Zin, Noor Hasniza (Universiti Teknologi Malaysia, 2015)
Seed storage proteins (SSPs) are the most important component in rice which provides nutrient to consumers. The SSPs content and composition are among the important determinant for rice quality determination specifically for nutritional value. Multiple factors have been identified to give effect to the nutritional value of rice grain including different types of rice. The purpose of this study is to investigate the expression level of SSPs of rice and also relates the nutrient quality of rice with the variability in SSPs expression from three different types of rice commercially available in markets. The SSPs were extracted from three different types of rice; white rice, brown rice and glutinous rice of the local rice brands in markets. Bradford Assay was carried out to determine the total SSPs content and brown rice was found to have significantly higher total SSPs content (9.157± 0.4 mg/100mg seeds) compared to white rice (6.933± 0.8 mg/ 100mg seeds) and glutinous rice (5.388± 0.2 mg/ 100mg seeds). Based on the banding patterns of the SDS-PAGE, there were different level of expressions were observed between the three rice types. The different expression can be observed obviously at the glutelin precursor region and glutelin acidic subunit region and prolamin polypeptides region for each type of rice. Therefore, contribute to the different nutritional value for dietary intake.